Prenatal diagnosis and outcomes of fetal teratomas. Issue 2 (1st October 2015) - Arisoy, Resul; Erdogdu, Emre; Kumru, Pinar; Demirci, Oya; Ergin, Nida; Pekin, Oya; Sahinoglu, Zeki; Tugrul, Ahmet Semih; Sancak, Selim; Çetiner, Handan; Celayir, Aysenur
ABSTRACT: Purpose: Our aim was to evaluate the diagnostic performance of ultrasonography (US) in the prenatal identification of teratomas and the perinatal outcome of the fetuses with those teratomas. Methods: In this retrospective case series study, we searched the archives using the keywords "fetal mass" or "fetal tumor" or "fetal teratoma" and "sacrococcygeal teratoma, " diagnosed between 2009 and 2014, within the US database of our center. Results: One hundred seven fetuses were prenatally diagnosed as having a cystic or solid mass, tumor, or teratoma. Nineteen of those cases were diagnosed prenatally as having fetal teratoma, but that diagnosis could not be verified in three cases. In one fetus, the prenatal diagnosis could not be confirmed. The sensitivity of US in identifying fetal teratoma was 100% and the false‐positive rate, 3.3%. Six pregnancies complicated by a fetal teratoma were terminated. A normal karyotype was identified in all fetuses that underwent karyotyping. Among the nine women who continued their pregnancy, polyhydramnios was identified in four fetuses; although high‐output heart failure was also identified in two of those fetuses during prenatal follow‐up, none developed hydrops. On delivery, nine infants were born alive, but three (33.3%) of them died within the early neonatal period. Conclusions: US has very high sensitivity and low false‐positive rates in identifying fetal teratoma prenatally. The risk of chromosomal abnormalities is very low in fetuses with teratoma, and their prognosis depends on the location and size of the tumor and any associated perinatal complications. © 2015 Wiley Periodicals, Inc. J Clin Ultrasound 44 :118–125, 2016